A new multirate LQ optimal regulator for linear time-invariant systems and its stability robustness properties - Arvanitis, Kostas G. (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, the LQ optimal regulation problem for continuous-time systems is solved by using a new class of multirate controllers, called Two-Point-Multirate Controllers (TPMRCs).
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka